CAPTURING THE 'PIONEERING MINDS' VIA HUMAN CAPITAL: THE IMPACT ON INNOVATIVE PERFORMANCE OF MALAYSIAN SMEs - Hasliza Abdul Halim,; Noor Hazlina Ahmad,; T. Ramayah,; Seyedeh Khadijeh Taghizadeh, (Asian Academy of Management Journal, 2016)
To cultivate “pioneering minds” is extremely important especially in the effort to shift Malaysia towards innovation-centered economy. The Malaysian government is confident of achieving the target provided that the human capital is leveraged in ensuring innovation at the highest level particularly among Small and Medium Enterprises (SMEs). Nevertheless, only few studies have considered human capital as a factor that mediates the effects of other variables on innovation. Therefore, this paper aims at investigating on how human capital dimensions namely uniqueness, value and pro-activeness will be leveraged by pro-innovativeness organisational architecture dimensions that is allocation for free time, work discretion, rewards, and tolerance for risk taking in order to achieve innovative performance. A structured study instrument was used for data collection purpose. A total of 1000 active SMEs were selected via simple random sampling from Malaysia Small and Medium Enterprises Directory 2011/12. A total of 263 SMEs responded to the questionnaire. However, a total of 262 usable questionnaires were thus secured for analysis. The analysis was then conducted via Partial Least Squares (PLS) structural equation modeling (SEM). The results showed several interesting findings: (a) rewards has an influence on the uniqueness, value and pro-activeness of human capital; (b) tolerance towards risk taking has an influence on human capital (uniqueness, value and pro-activeness; (c) uniqueness of human capital has an influence on innovative performance and (d) uniqueness of human capital mediated the relationship between tolerance for risk taking and innovative performance. The findings suggest that SMEs should put more focus on the reward system and tolerance for risk taking in order to encourage and enhance the 'pioneering mind' which in turn may increase innovative performance of SMEs.